Silicosis among grindstone cutters in the north of Nigeria. - Warrell, D; Harrison, B; Fawcett, I; Mohammed, Y; Mohammed, W; Pope, H; Watkins, B (1975)
Many of the grindstones used in Nigerian homes are quarried from sandstone in a small group of villages near Kano in the extreme north of the country. Of an unselected group of 126 stonecutters from two of these villages 49 were found to have radiographic evidence of silicosis, with progressive massive fibrosis in 17. Those with silicosis had worked longer in the quarries than 77 whose radiographs showed no evidence of silicosis. Sixty-three per cent of the silicotics had respiratory symptoms, the commonest being breathlessness on moderate exertion. Cough was the earliest symptom in 42%. Only 35% had abnormal physical signs in the cardiorespiratory system, 18% had clearly reduced ventilatory capacity, and airways obstruction was evident in 16%. The prevalence of silicosis in these open-cast sandstone quarriers is unexpectedly high. This is probably explained by the intensity of exposure and the particular kind of sandstone being worked. Reduction of dust exposure in these quarries raises severe practical problems, but the inhabitants of this drought-ridden area can scarcely be expected to abandon their traditional livelihood.